Translation directionality and translator anxiety: Evidence from eye movements in L1-L2 translation - Jia, Juan; Wei, Ziyu; Cheng, Heben; Wang, Xiaolu (Frontiers in Psychology, 2023)
While considerable research on the impact of anxiety on second language learning has been carried out in international contexts, the impact of anxiety on the translator’s undertaking L2 translation, a sort of anxiety arising from the translation directionality, as well as the structure of cognitive mechanism for translational anxiety, remain under-explored. Adopting the eye-tracking and key-logging approach to data collection, this study implemented an eye-tracking experiment with EFL learners at a Chinese university to probe into how the participants responded to L1 and L2 translation-tasks and the mechanism involved in these processes. It is found that translation directionality does have a great impact on the processing of translation, which causes the change of cognitive load and then leads to the change of levels in translator anxiety. The finding further confirms the key premises of the Processing Proficiency Model and the Revised Hierarchical Model with attendant implications for translation processes.